Pointing out the false autonomy of Brazilian municipalities: the “quality of the Federation” drawn by the Rule of Law and its impact on promoting the common good - Haeberlin, Mártin; Pasqualini, Alexandre (Revista de Investigações Constitucionais, 2022)
This paper addresses the problem of promoting the common good at the local governments. To demonstrate how Law should be seen primarily to a positive task (human flourishing), and to show how enaction and implementation of rights are strictly connected, it is presented the hypothesis in which the “quality of the Federation” (arrangement of competences, goods and incomes drawn in a Federal Rule of Law) is determinant in shaping a linear relation between the “ends elected” by a given community and the “means purposed” by the State administration to fulfill those ends. In this sense, the paper is divided in two sections, each one conducted from methodology of literary review and data analysis. The first section deals with the concept of common good and the perspective of using indicators to measure it. The second section takes the example of Brazilian Federation arrangement drawn in its Constitution to demonstrate the hypothesis. In the end, it is concluded that Brazil lives a false autonomy at the Municipalities level, and this false autonomy constitutionally designed can be a cause of genetic problems in achieving a dynamic of the common good.